Analysis of YouTube Content on Oral Disease Information about the Elderly - Ji-Won Kim; Hanna Gu; Hye-Jin Kwon; Jeong-Hyun Lim; Hee-Jung Lim (The Korean Society of Dental Hygiene Science, 2022)
Background: The elderly have, a higher disease morbidity than other age groups due to a decrease in resistance to the disease and have complex diseases, so care should be taken. Accordingly, it is considered important to provide information for improving the health of the elderly. Health information plays an important role in individual health promotion and education, so the degree of exposure to information about oral health of the elderly is expected to have a significant impact on understanding and acquiring information on oral content videos on the importance, prevention, and management of oral health of the elderly in the future.Methods: This study analyzed video content related to oral diseases of the elderly in a total of 150 videos uploaded on YouTube from January 1, 2012 to May 13, 2021, using a total of three books of dental hygiene for the elderly.Results: Forty-nine broadcasters accounted for the most of this information. Among the information providers, there were two dental hygienists. They accounted for 1.3% of all the information providers. The highest number of dental hygienists who broadcasted information was 42 in 2019. The average number of views was 37,303 periodontal diseases, the highest. Among the videos, dry mouth was the most common with 34 oral diseases.Conclusion: The number of images for each disease varies, so it seems that information should be provided in various ways. Dental hygienists should widely improve oral health knowledge by providing various dental hygiene management images for each oral disease to improve the oral health of the general public. In addition, based on the information of the Health Insurance Review and Assessment Service, the development and provision of content should be actively carried out so that people can obtain the information they desire.